Case report: Saccadic ping-pong gaze in progressive supranuclear palsy with predominant postural instability - Nunomura, Hikari; Kasahara, Taketoshi; Hatano, Taku; Shimada, Hitoshi; Takado, Yuhei; Endo, Hironobu; Inoshita, Ayako; Inomata, Atsuko; Murofushi, Toshihisa; Misawa, Shihoko; Machida, Yutaka; Imai, Hisamasa (Frontiers in Neurology, 2023)
We report a 63-year-old female patient with progressive supranuclear palsy (PSP). She presented predominant postural instability and “saccadic ping-pong gaze” (SPPG). She had unprovoked falls recurrently within a year from the onset of gait disturbance. She tended to fall backward with eye closure but had no freezing of gait on examination. She showed no signs of nuchal dystonia, limb tremor, rigidity, spasticity, or ataxia. The dopaminergic response was negative. On the initial examination, her vertical eye movements were normal, but frequent macro square wave jerks and SPPG were observed. SPPG consisted of short-cycle, horizontal conjugate irregular pendular oscillations of the eye position from the midpoint with superimposed small saccades. SPPG was observed usually in the dark, not in the daylight, and with eye closure by using electrooculogram and infrared charge-coupled device imaging. One and a half years after the first examination, she was diagnosed as probable PSP with vertical supranuclear gaze palsy. SPPG was first described in patients who are unconscious by Johkura in 1998 as a “saccadic” variant of “ping-pong gaze (PPG).” PPG, short-cycle periodic alternating gaze, has been described in comatose patients since 1967. On the other hand, abnormal eye movement, which looks the same as SPPG in coma, has been described in conscious patients with PSP or spinocerebellar degeneration (SCD) in Japanese literature since 1975. However, it has been called “transient alternating saccades (TAS).” Nowadays, we believe it is more appropriate to call this abnormal eye movement “SPPG” instead of TAS. Here, we propose that PSP, a neuro-degenerative disease, should be added as one of the etiologies of SPPG. We discuss the differences between PPG/SPPG in coma and SPPG in PSP and the possible pathophysiological mechanism of SPPG in relation to cerebellar oculomotor dysfunctions.